The Image of Paganism in the British Romanticism - Horák, Pavel (Pomegranate, 2018)
This article tries to answer the question of how the concept of Paganism was conceived and shaped by the Romantic thinkers, and whether it has influenced our current understanding of both antique Paganism and contemporary Paganism; if yes, how? My aim is to show this with the example of the Romantic period in the Great Britain especially between 1750–1850. I omit the commonplace account on the poets and other artists and their works in this paper, instead of that, I focus mainly on the works of antiquarians, historians, and philosophers, and want to show a different image of the Romantic period than it is often perceived. I start with the work of pre-Romantic antiquarian William Stukeley, and end with the work of Iolo Morganwg. The article argues that the very image of the ancient past was shaped by Christian theological concerns and questions, and the political situation and artistic romantic sentiment of the eighteenth and nineteenth centuries. Thus, the image of Paganism as it exists today reflects religious and political disputes of those centuries. The article also argues that not only has this image of Paganism has been retained till today, but that it has also influenced some notions of contemporary Pagan thought. This notwithstanding, the image of Paganism is no longer considered in its full scope, since the concerns and questions which guided its construction sank into oblivion, while their “product”— the romantic image of the Celts and Druids remained.